Experimental Comparison of Two Modifications of Activated Sludge for Treatment of Furfural-Containing Wastewater (Iranian Journal of Chemical Engineering)
A case study is presented in which two modifications of activated sludge treatment of complex chemical wastewater are experimentally compared: a combination of common activated sludge with powdered activated carbon treatment (PACT), and bioaugmentation of activated sludge treatment (BAST). Industrial wastewater of Pars Oil Refinery that was passed through an oil recovery stage was used to investigate the effect of furfural on two treatment processes in the range between 100-2000 ppm. Furfural was added manually. For comparison, furfural, COD, MLSS (Mixed Liquor Suspended Solids) concentrations and SVI (Sludge Volume Index) were measured daily. The results show a little higher COD removal efficiency in PACT system and the same furfural removal in both methods. But, it should be mentioned that at low HRT (Hydraulic Retention Time), BAST system showed better results in both furfural and COD removal than PACT system. SVI measurement shows that settability of effluent sludge in BAST system was always better than in PACT system. Because of rapid growth of microbial biomass in BAST system, the MLSS concentration in this modification was higher than in PACT system and in this way, BAST system has a lower requirement to return sludge than PACT system. Finally, it could be concluded that BAST system may be an attractive alternative to existing PACT system and if the former is used, it will result in both high performance and optimum conditions with economical operation.